IMPLEMENTASI KEBIJAKAN PROGRAM PENCEGAHAN PEMBERANTASAN PENYALAHGUNAAN PEREDARAN GELAP NARKOTIKA (P4GN) DAN PREKURSOR NARKOTIKA DI BNN KOTA TANGERANG - Nurhaliza, Maulani; Hardian, Dafyar Eliadi; Sentosa, Bambang Mardi (Perspektif : Jurnal Ilmu Administrasi, 2025)
This study aims to analyze the implementation of the Drug Abuse and Precursor Prevention and Eradication Program (P4GN) at the National Narcotics Agency (BNN) in Tangerang City. The research questions address the role of communication, resources, implementer disposition, and bureaucratic structure in implementing the P4GN program. This study employed a qualitative approach with a case study method. Data were obtained through in-depth interviews, observation, and documentation. Key informants included the head of the BNN in Tangerang City, technical implementation staff, and representatives from the National Unity and Politics Agency (Kesbangpol). Supporting informants included community leaders, anti-drug volunteers, and neighborhood administrators from the program's target areas. The SWOT analysis indicates that the BNN in Tangerang City's P4GN program falls into Quadrant I (Aggressive Strategy), with strengths in the institutional structure, regulatory support, and the enthusiasm of implementers, as well as opportunities from technological developments, cross-sector collaboration, and increased public awareness. Challenges arise from limited resources and weak synergy between agencies. To translate the SWOT strategy into measurable operational forms, a Balanced Scorecard (BSC) approach was used. The financial perspective focuses on budget efficiency and funding partnerships. The customer perspective focuses on increasing community participation. The internal process perspective emphasizes strengthening cross-agency coordination and standard operating procedures (SOPs). The learning and growth perspective focuses on enhancing human resource capacity and reward systems. These findings indicate the need for a holistic and measurable strategic approach to support the effectiveness of the P4GN program at the local level. Keywords: P4GN, policy implementation, SWOT, balanced scorecard, Tangerang City National Narcotics Agency, narcotics.